2015
DOI: 10.1542/peds.2014-2874
|View full text |Cite
|
Sign up to set email alerts
|

Timing of Opioid Administration as a Quality Indicator for Pain Crises in Sickle Cell Disease

Abstract: BACKGROUND AND OBJECTIVE: Time to opioid administration (TTO) has been suggested as a quality of care measure for sickle cell disease patients with vaso-occlusive crisis (VOC). We sought to determine whether TTO was associated with outcomes of emergency department (ED) visits for VOC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 29 publications
1
26
1
Order By: Relevance
“…IPPs have previously been shown to reduce pain scores and increase patient satisfaction. However, shorter time to initial opiate dose has not been associated with decreased admission rate which is consistent with our findings . Our time to initial opiate dose was stable (30 min pre IPP and 34 min post IPP).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…IPPs have previously been shown to reduce pain scores and increase patient satisfaction. However, shorter time to initial opiate dose has not been associated with decreased admission rate which is consistent with our findings . Our time to initial opiate dose was stable (30 min pre IPP and 34 min post IPP).…”
Section: Discussionsupporting
confidence: 91%
“…Our post‐intervention admission rate of 41% is lower that what has been previously reported in the literature. Previous studies of VOC in children have reported admission rates between 50 and 78% . We estimate that 49 admissions and 307 inpatient days are avoided annually through the initiative.…”
Section: Discussionmentioning
confidence: 97%
“…A discussion was held to ensure the ethical aspects of performing a placebo‐controlled trial as opposed to comparing INF to another medication. A review of the literature showed that time to first parenteral analgesia for children with a VOC in the PED is 52–90 min . A 2‐month chart review of children with SCD who presented to our PED with a pain score ≥6 found that the mean time from triage to intravenous access was 58 min, and the mean time from triage to first parenteral opiate was 104 min.…”
Section: Methodsmentioning
confidence: 97%
“…The outcomes of these interventions include improved pain management, hospital revenue, utilization of primary care clinics, and compliance with standard practice patterns and reduced admissions, length of stay (LOS), repeat ED visits, and 30-day readmission rates 6,17,2430. Consequently, developing a set of quality measures and implementing evidence-based practice (EBP) clinical guidelines have the potential to improve health outcomes of SCD 31,32…”
Section: Purpose and Review Of Literaturementioning
confidence: 99%